Question
upstudy study bank question image url

\( x^{2}-2 x y-3 y^{2}=0 \) and \( y-x=2 \)

Ask by Newton John. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( (x, y) = (-1, 1) \) and \( (x, y) = (-3, -1) \).

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}-2xy-3y^{2}=0\\y-x=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}-2xy-3y^{2}=0\\x=-2+y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(-2+y\right)^{2}-2\left(-2+y\right)y-3y^{2}=0\) - step3: Simplify: \(4-4y^{2}=0\) - step4: Move the constant to the right side: \(-4y^{2}=0-4\) - step5: Remove 0: \(-4y^{2}=-4\) - step6: Change the signs: \(4y^{2}=4\) - step7: Divide both sides: \(\frac{4y^{2}}{4}=\frac{4}{4}\) - step8: Divide the numbers: \(y^{2}=1\) - step9: Simplify the expression: \(y=\pm \sqrt{1}\) - step10: Simplify: \(y=\pm 1\) - step11: Separate into possible cases: \(y=1\cup y=-1\) - step12: Rearrange the terms: \(\left\{ \begin{array}{l}x=-2+y\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-2+y\\y=-1\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-3\\y=-1\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-3\\y=-1\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-1,1\right)\cup \left(x,y\right) = \left(-3,-1\right)\) To solve the system of equations given by: 1. \( x^{2} - 2xy - 3y^{2} = 0 \) 2. \( y - x = 2 \) we can find the solutions step by step. ### Step 1: Substitute \( y \) from the second equation into the first equation. From the second equation, we can express \( y \) in terms of \( x \): \[ y = x + 2 \] ### Step 2: Substitute \( y \) into the first equation. Now, substitute \( y = x + 2 \) into the first equation: \[ x^{2} - 2x(x + 2) - 3(x + 2)^{2} = 0 \] ### Step 3: Expand and simplify the equation. Expanding the equation: \[ x^{2} - 2x^{2} - 4x - 3(x^{2} + 4x + 4) = 0 \] This simplifies to: \[ x^{2} - 2x^{2} - 4x - 3x^{2} - 12x - 12 = 0 \] Combining like terms: \[ -4x^{2} - 16x - 12 = 0 \] ### Step 4: Multiply through by -1 to simplify. \[ 4x^{2} + 16x + 12 = 0 \] ### Step 5: Divide the entire equation by 4. \[ x^{2} + 4x + 3 = 0 \] ### Step 6: Factor the quadratic equation. Factoring gives: \[ (x + 1)(x + 3) = 0 \] ### Step 7: Solve for \( x \). Setting each factor to zero gives: \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \] \[ x + 3 = 0 \quad \Rightarrow \quad x = -3 \] ### Step 8: Find corresponding \( y \) values. Using \( y = x + 2 \): 1. For \( x = -1 \): \[ y = -1 + 2 = 1 \] 2. For \( x = -3 \): \[ y = -3 + 2 = -1 \] ### Final Solutions The solutions to the system of equations are: \[ (x, y) = (-1, 1) \quad \text{and} \quad (x, y) = (-3, -1) \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the system of equations \( x^{2} - 2xy - 3y^{2} = 0 \) and \( y - x = 2 \), we can first substitute \( y \) from the second equation into the first. From \( y - x = 2 \), we find that \( y = x + 2 \). We can substitute this expression for \( y \) into the quadratic equation: \[ x^{2} - 2x(x + 2) - 3(x + 2)^{2} = 0. \] Now, we can simplify the equation and solve for \( x \). Once we find \( x \), we can use it to find \( y \). Would you like me to proceed with the calculations, or do you have a specific aspect of this equation that you need further assistance with?

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy